2022
DOI: 10.1021/acs.iecr.1c04657
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Membrane Electrodialysis for Cleaner Production of Gluconic Acid: Valorization of the Regenerated Base for the Upstream Enzyme Catalysis

Abstract: Bipolar membrane electrodialysis (BMED) is an environmentally friendly, high-effective technique for the cleaner production of gluconic acid. However, the unsatisfactory purity and low concentration of the regenerated base limit the applicable field of the byproduct for further utilization. In this study, BMED was applied for the cleaner production of gluconic acid from the perspective of the regenerated base. First, four types of cation-exchange membrane were screened for the BMED process by evaluating the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…This phenomenon was abnormal compared with the various BMED studies in the literature. 30,31,33,35,36 Generally, the concentration of acid produced by BMED increased with an increase in current density because the water splitting rate was accelerated at high current density. 30,31,33,35,36 However, in our case, the discrepancy phenomenon is attributed to the competition transport between V 2 O 7 4− and OH − as well as the dissociation balance limitation of the polyvanadate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon was abnormal compared with the various BMED studies in the literature. 30,31,33,35,36 Generally, the concentration of acid produced by BMED increased with an increase in current density because the water splitting rate was accelerated at high current density. 30,31,33,35,36 However, in our case, the discrepancy phenomenon is attributed to the competition transport between V 2 O 7 4− and OH − as well as the dissociation balance limitation of the polyvanadate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…30,31,33,35,36 Generally, the concentration of acid produced by BMED increased with an increase in current density because the water splitting rate was accelerated at high current density. 30,31,33,35,36 However, in our case, the discrepancy phenomenon is attributed to the competition transport between V 2 O 7 4− and OH − as well as the dissociation balance limitation of the polyvanadate. At a low current density of 10−20 mA/cm 2 , there was little amount of water splitting OH − in the salt compartment due to a weak electric driving force.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Wang et al optimized the bipolar membrane electrodialysis for clean production of gluconic acid from the corresponding regenerated base, in terms of the type of cation-exchange membranes and operational parameters. 19 To facilitate the industrial application of nanofiltration diafiltration for effective separation of small molecules, Wang et al modeled and compared the energy consumption in the continuous feed diafiltration and intermittent feed diafiltration processes. 20 Xu et al reported an imine-bond-based reversible cross-linking approach for amine-terminated polybutadiene, giving rise to an easily recyclable telechelic rubber.…”
mentioning
confidence: 99%
“…By immobilizing poly­(ionic liquid) brushes on the surface of metal–organic-framework (MOF) UiO-66-(OH) 2 , Yang et al improved the dispersity of porous MOFs in poly­(ether- block -amide) matrix, producing mixed matrix membranes that manifest good separation selectivity and permeability for CO 2 and N 2 . Wang et al optimized the bipolar membrane electrodialysis for clean production of gluconic acid from the corresponding regenerated base, in terms of the type of cation-exchange membranes and operational parameters . To facilitate the industrial application of nanofiltration diafiltration for effective separation of small molecules, Wang et al modeled and compared the energy consumption in the continuous feed diafiltration and intermittent feed diafiltration processes .…”
mentioning
confidence: 99%